Treatment of pulmonary embolism: The use of low-molecularweight heparin in the inpatient and outpatient settings - Hull, Russell D. (Thrombosis and Haemostasis, 2008)
Pulmonary embolism (PE) remains a major clinical problem associated with considerable mortality and morbidity. In patients with PE, appropriate anticoagulant therapy has been shown to significantly reduce both recurrence and mortality. Low-molecular- weight heparin (LMWH) is at least as effective as unfractionated heparin (UFH) in the treatment of PE,with a similar risk of bleeding. Furthermore, LMWH offers more predictable pharmacokinetics and anticoagulant effects. As a result, current guidelines from both the American College of Chest Physicians and the joint American College of Physicians/American Academy of Family Physicians recommend the use of LMWH over UFH (in patients with submassive PE). Outpatient treatment with LMWH has been shown to be feasible in many patients,and offers the potential for cost-savings and improvements in healthrelated quality of life. Further data are needed to support an evidence- based recommendation for the use of LMWH in the outpatient treatment of PE.
Keywords: Anticoagulants; low-molecular-weight heparin; pulmonary embolism; thromboembolism